Anti-plane waves near an interface between two piezoelectric half-spaces. (July 2015) - Xu, L.M.; Wang, Xu; Fan, Hui
Highlights: The interface is modeled by a membrane with the surface/interface elasticity. Certain new waves propagate near an interface between two piezoelectric half-spaces. Configuration reduced into results, such as Love wave, Bleustein–Gulyaev wave. A complete picture of the anti-plane waves near the interfaces is provided. Full range effect of the interface in the anti-plane configuration is considered. Abstract: We show the existence of certain new waves that can propagate near an interface between two half-spaces of different piezoelectric ceramics, where the interface is modeled by a membrane with the surface/interface elasticity[1] . The current configuration can be reduced into a number of well-known results as special cases, such as Love wave, Bleustein and Gulyaev wave. Together with our previous work for the imperfect interface[2], a full range of consideration of the interface affecting the anti-plane waves is now completed.